2004
DOI: 10.1111/j.1467-6427.2004.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of couples‐based interventions for panic disorder with agoraphobia

Abstract: From this systematic literature review it was concluded that panic disorder with agoraphobia (PDA) can sometimes occur in conjunction with marital problems. Couples‐based treatments for PDA – partner‐assisted exposure and marital therapy – can be an effective treatment for the condition. It is as effective as individually based cognitive behaviour therapy. Involving partners of people with PDA in therapy may be appropriate in some cases, particularly those in which there are marital difficulties. Couple‐focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Considering the high prevalence of agoraphobia in spouses of HNC patients, two theoretical aspects may be helpful in better understanding this finding. First, the agoraphobic symptoms could be an expression of unconscious fear of losing the diseased partner, leading to a stronger attachment and/or dependency in the relationship with possible marital conflicts as a consequence which have been considered to be typical for agoraphobic individuals [35]. However, this aspect seems to be very unspecific and might be relevant for all cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high prevalence of agoraphobia in spouses of HNC patients, two theoretical aspects may be helpful in better understanding this finding. First, the agoraphobic symptoms could be an expression of unconscious fear of losing the diseased partner, leading to a stronger attachment and/or dependency in the relationship with possible marital conflicts as a consequence which have been considered to be typical for agoraphobic individuals [35]. However, this aspect seems to be very unspecific and might be relevant for all cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Effective familybased treatment aims to disrupt this process and enlist the aid of family members in helping the symptomatic person expose himself in a planned way to feared situations, and control his anxiety within these contexts. In a review of twelve studies of couples-based treatment for panic disorder for agoraphobia, Byrne et al (2004b) concluded that partnerassisted, cognitive-behavioural exposure therapy provided on a percase or group basis led to clinically significant improvement in agoraphobia and panic symptoms for 54 to 86 per cent of cases. This type of couples therapy was as effective as individually based cognitive-behavioural treatment, widely considered to be the treatment of choice.…”
Section: Panic Disordermentioning
confidence: 99%
“…Research supports the effectiveness of couples therapy in enhancing marital satisfaction (Johnson and Lebow, 2000; Shadish and Baldwin, 2003). In addition, recent research supports the effectiveness of couples therapy addressing ‘individual’ problems such as depression or anxiety, and it is seen as a context where partners can help each other grow and promote resilience (Baucom et al , 1998; Byrne et al , 2004; Leff et al , 2000). Many researchers have assessed various methods of treatment and have compared various models.…”
Section: Introductionmentioning
confidence: 99%